Fenomena tafsir tekstual dalam media sosial - Pratama, Yolan Hardika (Maliki Interdisciplinary Journal, 2023)
The propagation of religious teachings through social media has encompassed diverse content, including Quranic exegesis. However, the prevalence of textual exegesis on social media often overlooks vital aspects of the science of interpretation, such as historical context (asbabun nuzul), inter-verse coherence, abrogation (naskh mansukh), and linguistic expertise. This phenomenon is notably observed among Salafi accounts, where interpretations of verses frequently deviate from their original contexts. The primary cause of this inaccurate textual exegesis lies in the limited scholarly knowledge of interpretation among social media users. Furthermore, the textual exegesis approach is deemed simpler. Nevertheless, a more comprehensive understanding of textual exegesis, interpretive methodologies, and the role of scholarly authorities in Quranic interpretation can be explored in more in-depth articles.